Allodynia by Splenocytes From Mice With Acid-Induced Fibromyalgia-Like Generalized Pain and Its Sexual Dimorphic Regulation by Brain Microglia - Ueda, Hiroshi; Dozono, Naoki; Tanaka, Keigo; Kaneko, Shuji; Neyama, Hiroyuki; Uchida, Hitoshi (Frontiers in Neuroscience, 2020)
Fibromyalgia (FM), a disease of unknown etiology characterized by chronic generalized pain, is partly recapitulated in an animal model induced by repeated acid saline injections into the gastrocnemius muscle. Here we attempted to investigate the sex difference in pain hypersensitivity (mechanical allodynia and hypersensitivity to electrical stimulation) in the repeated acid saline-induced FM-like generalized pain (AcGP) model. The first unilateral acid injection into gastrocnemius muscle at day 0/D0 and second injection at D5 (post day 0, P0) induced transient and long-lasting mechanical allodynia, respectively, on both sides of male and female mice. The pretreatment with gonadectomy did not affect the first injection-induced allodynia in both sexes, but gradually reversed the second injection-induced allodynia in male, but not female mice. Moreover, the AcGP in male mice was abolished by intracerebroventricular minocycline treatments during D4-P4 or P5-P11, but not by early treatments during D0-D5 in male, but not female mice, suggesting that brain microglia are required for AcGP in late-onset and sex-dependent manners. We also found that the intravenous treatments of splenocytes derived from male, but not female mice treated with AcGP, caused allodynia in naive mice. In addition, the purified CD4+ T-cells derived from splenocytes of acid-treated male mice retained the ability to cause allodynia in naive mice. These findings suggest that FM-like AcGP has multiple sexual dimorphic mechanisms.